2007
DOI: 10.1051/0004-6361:20066757
|View full text |Cite
|
Sign up to set email alerts
|

Nonradial oscillations in classical Cepheids: the problem revisited

Abstract: Context. We analyse the presence of nonradial oscillations in Cepheids, a problem that has not been theoretically revised since the work of Dziembowski (1977, Acta Astron., 27, 95) and Osaki (1977, PASJ, 29, 235). Our analysis is motivated by a work of Moskalik et al. (2004, ASPC, 310, 498), which reports the detection of low-amplitude periodicities in a few Cepheids of the large Magellanic cloud. These newly discovered periodicities were interpreted as nonradial modes. Aims. Based on linear nonadiabatic sta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 9 publications
0
21
0
Order By: Relevance
“…However, linear pulsation calculations predict that in classical Cepheids all modes of < 4 should be heavily damped (Osaki 1977). This conclusion has recently been confirmed by new calculations of Mulet-Marquis et al (2007), who have found that all non-radial modes of < 5 should be damped. We note that this is a very different situation from that encountered in the RR Lyr models, where many modes of = 1, 2 are linearly excited (Dziembowski & Cassisi 1999).…”
Section: O N C L U S I O N Smentioning
confidence: 80%
“…However, linear pulsation calculations predict that in classical Cepheids all modes of < 4 should be heavily damped (Osaki 1977). This conclusion has recently been confirmed by new calculations of Mulet-Marquis et al (2007), who have found that all non-radial modes of < 5 should be damped. We note that this is a very different situation from that encountered in the RR Lyr models, where many modes of = 1, 2 are linearly excited (Dziembowski & Cassisi 1999).…”
Section: O N C L U S I O N Smentioning
confidence: 80%
“…To avoid the propagation of non-radial modes (Mulet-Marquis et al 2007) as much as possible, we chose a "small" box with an aspect ratio L x /L z = 1. If we refer to classical hydrodynamic instabilities, the critical horizontal wavelength λ crit from which instability develops is, in general, a bit larger than the vertical extent L z of the domain.…”
Section: Resultsmentioning
confidence: 99%
“…Their growth rates are at least an order of magnitude lower than for radial modes (Van Hoolst, Dziembowski & Kawaler 1998). Calculations for classical Cepheids (which are more massive) indicate that non-radial low degree modes are not excited (Mulet-Marquis et al 2007).…”
Section: Rv Tau Stars With Modulation Periods Closementioning
confidence: 88%